Analysis of Profit Expectations, Marketplace Utilization, and Islamic Buying and Selling Ethics on MSME Sales Performance - NUR ANISA HARAHAP; Nur Ahmadi Bi Rahmani; Faisal Umardani Hasibuan (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy and job creation. Along with the rapid development of digital technology, MSME actors are encouraged to utilize marketplaces to expand their customer base and increase sales. This study examines the impact of profit expectations, marketplace utilization, and the application of Islamic buying and selling ethics on the sales performance of MSMEs in Medan using a quantitative methodology. Likert-scale data were collected through questionnaires from 100 respondents, randomly selected from a population of 38,343 MSMEs registered in SIMDAKOP. The findings indicate that marketplace utilization, profit expectations, and Islamic buying and selling ethics all have a positive effect on sales and collectively account for 73.2% of the variance in sales performance. MSMEs are encouraged to enhance their use of marketplaces and continue implementing Islamic buying and selling practices to improve competitiveness and business sustainability; this will increase the likelihood that profit expectations will lead to higher sales.